Eco-Efficient Intensification of Potato with Bacillus subtilis and Trichoderma viride Under NPK Fertilization - Tueros Munive, Miguel Luis (2025)
Potato production in the Andean highlands demands strategies that reduce dependence on synthetic inputs without sacrificing yield. We evaluated two microbial bioinputs—Bacillus subtilis and Trichoderma viride—applied once pre-plant to seed tubers, under three organo-mineral fertilization regimes (0%, 50%, and 100% of the recommended NPK rate) in two cultivars (INIA 303-Canchán and Yungay) in field conditions in Ayacucho, Peru, using a randomized complete block, split-plot design (three replicates). Agronomic traits (plant height, root dry weight, stems per plant, tubers per plant, and plot-level yield) were analyzed with robust two-way ANOVA and multivariate methods. Combining microbial inoculation with 50% NPK sustained growth responses comparable to 100% NPK for key traits: in Yungay with T. viride, plant height at 50% NPK (≈96.15 ± 1.71 cm) was not different from 100% NPK (≈98.87 ± 1.70 cm), and root dry weight at 50% NPK (≈28.50 ± 0.28 g) matched or exceeded 100% NPK (≈16.97–22.62 g depending on cultivar–treatment). Notably, T. viride increased root biomass even without mineral fertilizer (≈27.62 ± 0.29 g in Yungay), while B. subtilis enhanced canopy vigor and stem number at full NPK (≈4.5 ± 0.29 stems). Yungay out-yielded INIA 303-Canchán overall (≈57.5 ± 2.5 kg vs. ≈42.7 ± 2.5 kg per plot). The highest yields occurred with B. subtilis + 100% NPK (≈62.88 ± 6.07 kg per plot), followed by B. subtilis + 50% NPK (≈51.7 ± 6.07 kg per plot). Plant height was the strongest correlate of yield (Spearman ρ ≈ 0.60), underscoring its value as a proxy for productivity. Overall, a single pre-plant inoculation with B. subtilis or T. viride can halve mineral fertilizer inputs while maintaining growth and sustaining high, cultivar-dependent yields in highland potato systems.